Joint Operating Agreements : A Comparison Between the IOC and NOC Perspectives, Second Edition /: A Comparison Between the IOC and NOC Perspectives, Second Edition. (2022) - Pereira, Eduardo G; Ovcharova, Anna; Fowler, Reg
No abstract available